ERUPTIVE VARIABLES IN THE GALACTIC HALO - HARO, G; CHAVIRA, E (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1960)
We present preliminary information about 7 of the blue variables discovered in the galactic halo.
BOL OBS TONAN TACUB
Keywords: ERUPTIVE, VARIABLES, GALACTIC HALO; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS